PROBLEMS AND SOLUTIONS FOR ENHANCING INDIVIDUAL SPIRITUAL PERFECTION IN THE PROCESS OF NATIONAL DEVELOPMENT - Karimova Mukhlisa Azizbek qizi (Web of Journals Publishing, 2025)
The article examines the strategic objectives of raising the spiritual maturity of the individual at a new stage of development of Uzbekistan, the social goals of education and upbringing policy, as well as current socio-philosophical problems of raising the spiritual culture of the individual and their solutions.
Keywords: Independent personality, theorists, cultural values, “trinity of truth, goodness and beauty”, freedom, creativity, awakened conscience.